Synthesis and kinetic evaluation of analogs of (E)-4-amino-3-methylbut-2-en-1-yl diphosphate, a potent inhibitor of the IspH metalloenzyme - Petit, Benoît Eric; Jobelius, Hannah; Bianchino, Gabriella Ines; Guérin, Mélina; Borel, Franck; Chaignon, Philippe; Seemann, Myriam (Comptes Rendus. Chimie)
Our previous research revealed that (E)-4-amino-3-methylbut-2-en-1-yl diphosphate (AMBPP) is one of the best inhibitors of IspH, a [4Fe–4S]-dependent enzyme involved in the methylerythritol phosphate pathway that is a valuable target for the discovery of new antibacterial and antiparasitic drugs as it is absent in humans. AMBPP has substantial limitations for drug development due to its poor metabolic stability. Here, we investigate the replacement of the diphosphate moiety of AMBPP by more stable mimics: sulfonate, phosphonate or phosphinophosphonate. After synthesis of the derivatives, enzymatic assays demonstrated that none of these AMBPP analogs is an efficient IspH inhibitor.